Síndrome hepatorrenal - Bardi S., Alberto (Revista Hospital Clínico Universidad de Chile, 1996)
HEPATORRENAL SYNDROME In this article the author presents the definition, clínica[ features, laboratory findings, pathophysiology and management of the Hepatorrenal Syndrome.